2018
DOI: 10.1182/blood-2018-99-116283
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Restoration of T and NK Cell Compartment after Venetoclax Treatment

Abstract: Introduction Chronic lymphocytic leukemia (CLL) is characterized by a profound immune suppression. In addition, CLL cells evade immune destruction by interacting with cells of the adaptive immune system, resulting in dysfunctional T cells. CD4+ T cells are skewed towards a TH2-profile and the number of regulatory T (Treg) cells, that diminish cellular immune responses, is increased in CLL patients. CD8+ T cells resemble exhausted T cells and have reduced cytotoxic, yet increased cytokine product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In common with other cancers, it might be expected that Tregs play their biggest role at sites of disease, however the limited studies on lymph nodes in CLL have provided contradictory findings; no evidence for presence of Tregs (Patten et al, 2008) but increased frequency of Tregs in lymph nodes relative to peripheral blood in other studies (Hartmann et al, 2015;de Weerdt et al, 2018). While it is difficult to assign any direct role of Tregs in CLL disease, it is possible that their biggest impact might be indirect.…”
Section: Regulatory T Cells and Other Cd4 Subsetsmentioning
confidence: 99%
See 1 more Smart Citation
“…In common with other cancers, it might be expected that Tregs play their biggest role at sites of disease, however the limited studies on lymph nodes in CLL have provided contradictory findings; no evidence for presence of Tregs (Patten et al, 2008) but increased frequency of Tregs in lymph nodes relative to peripheral blood in other studies (Hartmann et al, 2015;de Weerdt et al, 2018). While it is difficult to assign any direct role of Tregs in CLL disease, it is possible that their biggest impact might be indirect.…”
Section: Regulatory T Cells and Other Cd4 Subsetsmentioning
confidence: 99%
“…Ex vivo analysis of samples from patients treated with venetoclax demonstrated a maintenance of absolute T cell numbers, but a decrease in proportion and absolute number of Treg cells. There was also an effect on the CD8 compartment, with fewer CD8 + PD‐1 + T cells and lower proportions of CD8 T cells capable of secreting interferon‐γ (IFNγ) and tumour necrosis factor‐α (TNFα) (de Weerdt et al , ). Although further studies are needed to validate these results, they suggest the targeting of CLL cells by venetoclax has a beneficial effect on the T‐cell compartment.…”
Section: Impact Of Treatment On T Cells In Cllmentioning
confidence: 99%
“…Both ibrutinib and venetoclax have been reported to reduce tumor pro-survival Tfh and T-reg cells and reactivate T-cells as monotherapies [50,78]. The combination of both molecules has been studied in patients with CLL with results reaching superior complete responses and MRD negativity [79].…”
Section: Other Combinationsmentioning
confidence: 99%
“…In addition to their direct effects on CLL cells, several small-molecule inhibitors were reported to improve the function of non-malignant immune cells. Ibrutinib and venetoclax are two compounds associated with immune recovery in CLL patients [104,105]. Although there are less data on the effect of venetoclax, current results indicate that both ibrutinib and venetoclax treatment lead to a decrease in tumor-supportive T fh and T reg cells, while also reducing T-cell exhaustion [104,105].…”
Section: Responses To Immunotherapy In Cllmentioning
confidence: 99%
“…Ibrutinib and venetoclax are two compounds associated with immune recovery in CLL patients [104,105]. Although there are less data on the effect of venetoclax, current results indicate that both ibrutinib and venetoclax treatment lead to a decrease in tumor-supportive T fh and T reg cells, while also reducing T-cell exhaustion [104,105]. Therefore, combination treatment of immunotherapy with small-molecule inhibitors may have beneficial effects, and multiple studies reported on these combinations.…”
Section: Responses To Immunotherapy In Cllmentioning
confidence: 99%